Multi-source feedback in undergraduate medical education: a pilot study - Bartman, Ilona; St-Onge, Christina; Roy, Marguerite; Gingerich, Andrea; Katsoulas, Eleni; Chahine, Saad; Gagnon, Nathalie (Canadian Medical Education Journal, 2025)
Background: Multisource feedback (MSF) and 360-degree assessment collate feedback from multiple perspectives for a particular person. Since MSF aligns with programmatic assessment, undergraduate programs could theoretically incorporate this practice. This paper details the creation of an undergraduate medical education (UGME) MSF and its initial pilot. Methods: The Medical Council of Canada (MCC) collaborated with researchers from four Canadian UGME programs to adapt an existing tool, MCC 360. They adjusted MSF components for clerkship and piloted the revised version at one Canadian medical school. Student participants completed a post-evaluation survey. Researchers chose the Norcini et al. framework to inform the tool adaptation and evaluation. Results: The new MCC 360 UGME incorporated MSF from three rater groups (patients, self, and a mixed group of supervisors, residents, hospital staff and/or peers) and compiled it into an individualized report. An independent facilitator reviewed and discussed the report with the student. Students indicated that the MCC 360 UGME had a major to moderate impact on their learning. They appreciated receiving patient feedback and working with facilitators to identify areas of improvement. Although students found completing the MSF requirements to be burdensome, they found it to be acceptable to provide educational benefits. Conclusion: Implementing MSF in Canadian UGME would allow clerkship students to access feedback from patients and others in the workplace. It would also socialize students to MSF early in their careers.